Tomato SlYTH1 encoding a putative RNA m6A reader affects plant growth and fruit shape. (October 2022) - Yin, Shuangqin; Ao, Qiujing; Qiu, Tiaoshuang; Tan, Caiyun; Tu, Yun; Kuang, Tianyin; Yang, Yingwu
Abstract: N 6 -methyladenosine (m 6 A), the most abundant and common modification on eukaryotic mRNA, plays crucial roles in multiple biological processes through controlling endogenous gene activity in organisms. The m 6 A reader specifically recognizes the m 6 A mark to mediate the regulation of m 6 A on mRNA, and determines the fate of its target mRNA. In plants, the currently confirmed m 6 A readers are YTH (YT521B homology) domain-containing proteins. We previously reported that tomato contains 9 YTH genes, of which SlYTH1 has the strongest expression. The present study reports the functional characterization of SlYTH1 in tomato. SlYTH1 mutants generated via CRISPR/Cas9 technology exhibited pleiotropic phenotypes, including low seed germination rate, shortened seedling root, retarded plant growth and development during vegetative development, and elongated and longitudinally flattened fruit with reduced the locule number. SlYTH1 knockout reduced GA3 content and downregulated the expression of related genes in gibberellin biosynthesis pathway. Moreover, exogenous GA3 application could partially restore the phenotypic defects caused by SlYTH1 mutations. SlYTH1 knockout could alleviate the inhibition of seedling root elongation by exogenous GA3 application at relatively low concentration. These facts indicated SlYTH1 is involved in regulating gibberellin biosynthesis and plays important roles in multiple physiological processes in tomato. Highlights: Tomato SlYTH1 knockout reduced seed germination rate, and retarded plant vegetative development. SlYTH1 mutations produced elongated and longitudinally flattened fruit with reduced the locule number. SlYTH1 mutations reduced GA3 content, and exogenous GA3 could partially rescue the phenotypic defects of SlYTH1 mutants.